Path Following Control of an AUV under the Current Using the SVR-ADRC - Zheping Yan; Yibo Liu; Jiajia Zhou; Di Wu (Journal of Applied Mathematics)
A novel active disturbance rejection control (ADRC) controller is proposed based on support vector regression (SVR). The SVR-ADRC is designed to force an underactuated autonomous underwater vehicle (AUV) to follow a path in the horizontal plane with the ocean current disturbance. It is derived using SVR algorithm to adjust the coefficients of the nonlinear state error feedback (ELSEF) part in ADRC to deal with nonlinear variations at different operating points. The trend of change about ELSEF coefficients in the simulation proves that the designed SVR algorithm maintains the characteristics of astringency and stability. Furthermore, the path following errors under current in simulation has proved the high accuracy, strong robustness, and stability of the proposed SVR-ADRC. The contributions of the proposed controller are to improve the characteristics of ADRC considering the changing parameters in operating environment which make the controller more adaptive for the situation.